Case study on patient with CSOM with intracranial and intratemporal complications managed with craniotomy and facial nerve decompression - Prinja, Sumit; Davessar, Jai Lal; Singh, Gurbax; Singh, Harinder; Khurana, Vatika; Midha, Nupur (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Facial nerve palsy, together with the intracranial abscess and labyrinthitis is a representative complication of advanced middle ear cholesteatoma. It is rare now a day due to ready access to medical care and antibiotics. Facial palsy is not life threatening but impairs facial movement and markedly affects patient’s social life and causes serious psychological damage. Appropriate management of this complication is necessary to ensure healing without sequelae. We present a case of CSOM with intracranial and intratemporal complications. The patient had undergone craniotomy for intracranial abscess drainage and underwent facial nerve decompression by transmastoid approach.